Odpowiedzi

Najlepsza Odpowiedź!
  • kb93
  • Początkujący
2010-04-13T16:38:03+02:00
A) -4x-7-3x+7 = - 7x
b) x-2xy+1/2x-1/3xy = - 2⅓ xy + 1½x
c) -x2( do kwadratu ) +y2 ( do kwadratu ) - 2y2 ( do kwadratu )= - x² - y²
d) -x2( do kwadratu ) + 2x - 3x + x2 ( do kwadratu ) = -1x
e) 4x+4-7x-1/2 = - 3x + 3½
f) -2ab + 12a - 4ab - 16a = - 6ab - 4a
1 5 1
2010-04-13T16:39:04+02:00
A) -7x
b) - 2(całe) i 1/3(jedna trzecia) xy
c) -x(do kwadratu)-y(do kwadratu)
d) -x
e) -3x-2
f) -6ab-4a
2010-04-13T16:39:42+02:00
A) -4x-7-3x+7
-7x
b) x-2xy+1/2x-1/3xy
1 1/2x -1 2/3xy
c) -x( do kwadratu ) +y( do kwadratu ) - 2y ( do kwadratu )
xy(do kwadratu) + (-y) (do kwadratu)
d) -x( do kwadratu ) + 2x - 3x + x ( do kwadratu )
-x
e) 4x+4-7x-1/2
-3x+3 1/2
f) -2ab + 12a - 4ab - 16a
-6ab+(-4a)